MAXIMUM UTILIZATION OF SOLAR RADIATION USING SUN TRACKING SYSTEM. - MANOJ, VASUPALLI; PRATHYUSHA, MUNAGAPATI; REDDY, B. S. VAMSI KRISHNA (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Sun Tracking System for Solar panel project is made to tracking the Sun at day time for utilizing its solar energy properly for solar panel. The Sun trackers are all-weather, reliable and affordable tracking and positioning instruments. This project orients the Solar Panel toward the sun, so that it can utilize with higher accuracy. Our Sun Tracker system track the Sun by use of sensors and rotate the solar panel by means of stepper motor. For flat-panel applications, trackers are used to minimize the angle of incidence between the incoming light and a solar panel. This increases the amount of energy produced from a fixed amount of installed power generating capacity. The optics in concentrated solar applications accepts the direct component of sunlight light and therefore must be oriented appropriately to collect energy. Tracking systems are found in all concentrator applications because such systems do not produce energy unless oriented closely toward the sun.